Building adaptive capacity to impacts of climate change related disaster risk the case of urban barangays of Coron, Palawan - Fababeir, Michael Adrian F. (School of Urban and Regional Planning, University of the Philippines Diliman, 2018)
Climate change has become a serious challenge for different communities around the world, and its adverse impacts are increasingly being felt particularly by developing countries, where urbanization is rapidly happening. It comes in different forms, such as temperature rise, variability of precipitation, increase and intensity of typhoons, and sea level rise, which may trigger droughts, floods, heat waves and forest and grassland fires. These climate change impacts greatly affect a community's economy and well-being. As a result, it becomes more important for communities to learn how to adapt to these impacts. Super Typhoon Yolanda (International Name: Haiyan) was one of the strongest and deadliest tropical cyclones that made landfall in the Philippines. Its effects were considered the true impacts of climate change, as thousands of livelihoods were disrupted and an equal number of lives were destroyed. The Munipality of Coron, Palawan, situated at the coastal area with tourism as its major source of livelihood, is one of the areas that was greatly affected by the super typhoon. This study aims to determine the mechanisms that should be established by the urban coastal barangays of the municipality in order to build their adaptive capacity, by (1) looking at the effects of Yolanda in these barangays, (2) assessing the perception of the community on climate change adaptation (CCA) and disaster risk reduction and management (DRRM)in the municipality, and (3) evaluating the adaptive capacity measures the local government carried out when Yolanda hit these barangays. Results from the survey, key informant interview, focus group discussion, documentary review and ocular inspections show that the five (5) identified urban coastal barangays in the municipality (Poblacion 1, Poblacion 2, Poblacion 3, Poblacion 5, and Tagumpay) have low adaptive capacity to address the impacts of climate change-related disaster risks. This was apparent when Yolanda struck, where barangays experienced significant destruction because of insufficient proactive measures by the government to alleviate the deadly impacts of the super typhoon. Mainstreaming CCA and DRRM into the local plans is found to be of utmost importance to the municipality. This becomes an opportunity for the local government to empower communities to be aware and knowledgeable about CCA and DRRM to further enhance involvement, as well as enact policies that would build or increase the adaptive capacity of Coron such as the strict implementation of a "no building policy" along the 20-meter easement in the coastal area, building of houses using concrete materials, and the use of a more systematic early warning signal system, among others.